Is a European Recovery Possible Without High-Tech Public Corporations? - Daniele Archibugi; Vitantonio Mariella (Intereconomics)
Abstract Pervasive new technologies associated with information and communication technologies and software are dominated by a restricted oligopoly of US-based corporations. The challengers are no longer European firms, but rather Japanese or Chinese companies. The actions taken by the EU to fill this technology gap, including the Framework Programmes for research and technological development, are beneficial but still insufficient in terms of the resources committed. This article argues that the EU urgently needs to add another economic policy instrument to defy these incumbent firms, namely to create a few publicly supported large corporations in the areas of greater scientific and technological opportunities. This will be complementary to the already ongoing mission-oriented innovation policies. While there are the political and economic difficulties of implementing such a strategy, one recalls the pioneering venture of Airbus, established more than 50 years ago that has successfully managed to challenge the dominant US-based passenger aircraft producers despite several economic and political controversies. Could similar attempts be replicated for green technologies, healthcare services and artificial intelligence?